2023
DOI: 10.1038/s42949-023-00095-z
|View full text |Cite
|
Sign up to set email alerts
|

Japanese urban household carbon footprints during early-stage COVID-19 pandemic were consistent with those over the past decade

Abstract: As urbanization accelerates worldwide, substantial energy and services are required to meet the demand from cities, making cities major contributors to adverse environmental consequences. To bridge the knowledge gap in the absence of fine-grained city-level climate protection measures due to data availability and accuracy, this study provides a detailed carbon emission inventory for analyzing the monthly fluctuations based on citizens’ daily consumption behaviors. Here, carbon emissions embodied in approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…A previous study identified gasoline, kerosene, LPG, and city gas as the primary fossil fuels responsible for direct emissions from Japanese households 41 , 54 . The fundamental principles for calculating the direct emissions from the use of different fuels are presented here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study identified gasoline, kerosene, LPG, and city gas as the primary fossil fuels responsible for direct emissions from Japanese households 41 , 54 . The fundamental principles for calculating the direct emissions from the use of different fuels are presented here.…”
Section: Methodsmentioning
confidence: 99%
“…To validate the accuracy of our study, we consulted carbon footprint data from several government agencies, including the GHG Emissions Data of Japan from the Greenhouse Gas Inventory Office of Japan (GIO) 68 at the National Institute for Environmental Studies (NIES), the National Household CO 2 Survey from the Japan Society of Energy and Resources, and a previous study 54 . The detailed results of these comparisons by year and month are shown in Fig.…”
Section: Technical Validationmentioning
confidence: 99%